Thin-walled structure acoustic excitation response and fatigue life investigation in high temperature. (September 2021) - Wang, Jian; Huang, Zhiyong; Sha, Yundong; Shen, Jiebin; Yu, Chuanli
Highlights: High temperature and strong noise test was successfully carried out. A new fatigue life model included the improved rain flow counting method was derived. The rapidly alternate heating and cooling load will greatly affect the fatigue life. The valley position of the fatigue life shifts to the right in the heating process. Abstract: The cyclic stress produced by rapidly alternate heating and cooling and strong noise on the combustion chamber of aero-engineer will seriously affect its fatigue performance. In order to explore the influence of the load on the first-order thermal modal frequencies and fatigue resistance, the high temperature and strongly acoustic excitation response test and fatigue test for Haynes alloy 188 thin-walled structure with the rapidly alternate heating and cooling were firstly carried out for various work conditions. Based on the coupled finite element and boundary element methods to calculate the dynamic response, the comparison is discussed about the modal frequencies and strain values between the simulation and test. A fatigue life model included the improved rain flow counting method and miner linear damage accumulation theory was proposed to predict the fatigue life of the thin-walled structure. The prediction results are verified by comparing the fatigue damage and fatigue life with the tests. The simulation reveals that in higher temperature the nonlinear response of the structure is expanded significantly, and the rapidly alternate heating and cooling load aggravates the vibration behavior, reducing the fatigue life and making the valley position of the fatigue life shift to the right in the heating process.